HUBUNGAN PENGETAHUAN DAN SIKAP TERHADAP TINDAKAN TENTANG PAP SMEAR DAN INSPEKSI VISUAL ASETAT PADA WANITA PEKERJA SEKSUAL TIDAK LANGSUNG DI HOTSPOT X KECAMATAN MARPOYAN DAMAI PEKANBARU SEBAGAI DETEKSI DINI KANKER SERVIKS - Abdul Aziz; Wiwit Ade Fidiawati; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2016)
ABSTRACTCervical cancer is a malignancy grows in the cervix. Cervical cancer ranks as the fourth most common cancer in women worldwide. This disease can be detected early by Pap smear and Visual Inspection with Acetic Acid (VIA). Indirect female sex worker (FSW) have a higher risk of cervical cancer. The aim of this study is to reveal the correlation between knowledge and attitude towards the behaviour of indirect FSW at hotspot X District Marpoyan Damai Pekanbaru about Pap smear and VIA as an early detection of cervical cancer. The method of this research is analytic corss sectional. Population is indirect FSW living in the hotspot X and samples were taken with total sampling method to 43 people trough interviews using questionnaire. The results showed that among 43 FSWs, 28 people (65.1%) aged less than 26 years old, 25 people (58.2%) have Junior High School (JHS), 21 people (48.8%) have poor knowledge, 24 people (55.8%) have a negative attitude and 33 people (76.7%) did test. There is no correlation between knowledge and attitude (p=0.063), no correlation between knowledge and behaviour (p=1.000) and no correlation between attitude and behaviour (p=0.302). it is concluded that the majority of indirect FSW at hotspot X have bad knowledge, negative attitude but have behaviour an early detection of cervical cancerKeywords: Knowledge, Attitude, Behaviour, Cervical Cancer, Indirect Female Sex Worker, Pap Smear, VIA, Hotspot X